2021
DOI: 10.3390/ijerph18189929
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Depression and Risk of Post-Traumatic Stress Disorder in Health Workers: The Relationship with Burnout during COVID-19 Pandemic in Italy

Abstract: During the COVID-19 pandemic, healthcare workers (HW) have faced an extremely difficult work environment, with an increased workload and traumatic events. Our study aimed to investigate the impact of COVID-19 pandemic on HW’s mental wellbeing. We analyzed the correlations between levels of burnout and other mental health disorders and we searched for the presence of specific risk factors of post-traumatic symptomatology related to the pandemic. A structured an on-line questionnaire and validated instruments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 48 publications
(51 reference statements)
2
17
1
5
Order By: Relevance
“…A survey conducted within the framework of the COVID-19 HEROES initiative in Spain, a country close to Italy in terms of geography, culture, and organization of services, found that 27% of the HCWs interviewed screened positive at the PHQ-9 and 74% at the GHQ-12 ( 36 ). The lower estimates in our study can be explained by the fact that we collected data during the re-opening phase after lockdown, when the number of COVID-19 cases and thus the workload of HCWs were decreasing, while in Spain and the other studies cited data were collected during the first wave ( 36 , 41 , 42 ) or at the beginning of the second wave ( 43 , 44 ). Furthermore, we decided to adopt a very high cut-off both for the PHQ-9 (scores ≥ 15) and the GHQ-12 (scores ≥ 4 using the bimodal scoring method), while for instance, the Spanish group adopted lower cut-offs (PHQ-9 > 9 and GHQ-12 > 2) ( 36 ).…”
Section: Discussioncontrasting
confidence: 58%
“…A survey conducted within the framework of the COVID-19 HEROES initiative in Spain, a country close to Italy in terms of geography, culture, and organization of services, found that 27% of the HCWs interviewed screened positive at the PHQ-9 and 74% at the GHQ-12 ( 36 ). The lower estimates in our study can be explained by the fact that we collected data during the re-opening phase after lockdown, when the number of COVID-19 cases and thus the workload of HCWs were decreasing, while in Spain and the other studies cited data were collected during the first wave ( 36 , 41 , 42 ) or at the beginning of the second wave ( 43 , 44 ). Furthermore, we decided to adopt a very high cut-off both for the PHQ-9 (scores ≥ 15) and the GHQ-12 (scores ≥ 4 using the bimodal scoring method), while for instance, the Spanish group adopted lower cut-offs (PHQ-9 > 9 and GHQ-12 > 2) ( 36 ).…”
Section: Discussioncontrasting
confidence: 58%
“…In particular, burnout is a common syndrome in HCWs amid the pandemic. While burnout syndrome is not included in the list of mental disorders in the 10th revision of the International Classification of Diseases, a study suggested its association with major mental disorders such as insomnia, depression, anxiety, and post-traumatic symptoms [ 7 ]. We previously reported that HCWs who engaged in care of COVID-19 patients had significantly higher burnout rates (50.0%) than those who did not, and those working in the intensive care unit were more likely to have experienced burnout than those in floors [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These excellent results on users' and MHW' satisfaction were recorded in Italy, while the health staff of non-psychiatric agencies experienced stress and frustration [34]; Lasalvia et al [35] found that 53.8% (95% CI [51.0-56.6%]) of health care workers showed symptoms of post-traumatic distress, 50.1% (95% CI [47.9-52.3%]) symptoms of clinically relevant anxiety and 26.6% (95% CI [24.7-28.5%]) of at least moderate depression. Similarly, Rossi et al [36] found that 49.4% of health workers showed symptoms of post-traumatic stress disorder, 24.7% symptoms of depression, and 19.8% symptoms of anxiety; at the same time there was a substantial distrust of the population towards the health system as a whole [37].…”
Section: Discussionmentioning
confidence: 85%